AN ANALYSIS OF DAMAGE ON TUBE REFORMER BY USING COMPUTATIONAL FLUID OF DINAMICS (CFD) METHOD - Amir; Rahdiana, Nana; Endah Wahyuni, Ayu (International Journal of Psychosocial Rehabilitation, 2020)
Reformer is a reactor that happened a “steam reforming” reaction. The reaction involves natural gas and steam or water. That Reformer works to break hydrocarbon become hydrogen. reforming is a reaction process of CH4 + H20 CO + 3H2 that needs a temperature dan high-pressure, that reformer is operated at 800- 1000ºC and pressure 2.1 kg/cm2. It is caused the operational has a high temperature, thus, there is the enduring a symptom of reports of damage or injuries in the sight of elbow carburizing. The damage is caused by some factors, such as oxidation, carburazing (metal dusting), nitridasi, corrosion by halogen, corrosion by molten metal and deposit ashes or salts Carburization (metal dusting), Creep, Thermal shock, Prolong overheating, and Short term overheating. The causes of damage are in the sight of elbow tube reformer and CFD (Computational Fluid Dynamic) simulation. Based on the analysis of CFD simulation, then the elbow of the tube reformer that undergo oxidation, which means erosion corrosion due to thinning of the elbow is uneven and the formation of small particles resulting in the erosion of material at the elbow reformer tube, to Perform a precautionary measure, it is in the area elbow granted coating the surface with a coating of boron carbida, in order to obtain a surface layer that is resistant to wear and low friction and is also resistant to erosion, surface coating on the side of the elbow can be done by way of boron carbide coating thickness of 05 μm - 1.00 μm to obtain a surface hardness high and high wear resistance and a low friction korfisien. Perform routine maintenance in accordance with the operational requirements of managing and maintaining the operational gas flow rate is maintained.